Strategi Sistem Branding Pemasaran untuk Meningkatkan Kunjungan Pelanggan di Sektor Dua Cafe & Resto - Varina, Eka Lailita Eti; Rini, Asih Setyo; Afansya, Helmalia; Rahmatulloh, Imam; Avrilia, Pingki; Fiddin, Setyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research was conducted at Sektor Dua Cafe & Resto by analyzing effective strategies to boost customer visits through improvements in the branding system at Sektor Dua Cafe & Resto. The methods used included observation and quantitative research by distributing questionnaires to 106 customers. Based on the research conducted, the first results obtained include data on customer satisfaction recap based on their experiences at Sektor Dua Cafe & Resto, social media performance results, a recap of best-selling menu items and the number of items sold in December 2024, event poster design results, and finally, several changes to seating areas and the addition of new features at Sektor Dua Cafe & Resto, aimed at enhancing comfort and increasing the number of visitors.